Project and desire of being teacher of physical education in public schools: an study about teaching and pedagogical investment - Artur Gomes de Souza; Justina Inês Sponchiado; Fabio Machado Pinto (Universidade Federal de Santa Catarina, 2017)
This paper had as study object the pedagogical investment of the teacher. We investigated the trajectory and the practices of one female teacher that works for 13 years in basic education. We used the biographic and ethnographic approach, as resource to semi-structured interview and observations of 24 classes taught by that teacher. The Sartrean categories of project and desire of being and, also, the concept of mobiles that, according to the Soviet School, give sense to the subject activity, were used in the data analyses refered to the trajectory and pedagogical investment. We identified that the fundamental mediations in her project achievement and the reasons that incites to act in an permanent basis of adversity and accomplishments.